Komunikasi Antarpribadi Orang Tua dan Mahasiswa Rantau dalam Mengatasi Konflik Komunikasi Jarak Jauh - Akbar, Shakira; Candrasari, Satya (UNIVERSITAS KALBIS, 2024)
Interpersonal communication between parents and overseas students that are rare and less intensive, as well as limited distance and time, will lead to long-distance communication conflicts. The purpose of this study was to determine the interpersonal communication of parents and overseas students in overcoming long-distance communication conflicts. This study uses Deception theory using descriptive qualitative research methods and the post positivism paradigm. The category of informants in this study were key informants of overseas students who left their area of origin. The results of this study indicate that long-distance communication conflicts between parents and overseas students can be overcome by consistent long-distance interpersonal communication. Interpersonal communication in conflict resolution can be said to be effective, the way parents and overseas students deal with long-distance communication conflicts must have an attitude of openness, empathy, support, positive feelings and equality.